Building cross-platform mobile apps with Xamarin and Visual Studio LiveLessons (Sneak Peek Video Training) : share your app's code base between iOS, Android and Windows Phone - Sells, Chris (Addison-Wesley, 2014)
"The world is no longer a homogeneous place for software development. Gone are the days when you could target Windows and hit the majority of your potential users, especially for consumer apps. Today's consumers are overwhelming running iOS and Android, primarily phones, but increasingly tablets. Until recently, if you wanted to build a native app to target both mobile platforms, you'd be using a Mac, XCode and Objective-C to build for iOS and Eclipse and using Java to build for Android, with no shared code. Or, if you were a Windows developer, you could use Xamarin inside of Visual Studio and share .NET libraries between your iOS and Android versions, but you'd be building your UI twice -- once for each platform. Now, with the release of Xamarin 3, it's possible to build your entire app in a way that's shared between iOS, Android and Windows Phone. For the first time, you can share the entire code base of an app between the three platforms, not just some libraries. This course will show how to build a real-world mobile app targeting iOS, Android and Windows Phone using Xamarin 3 integrated with Visual Studio."--Resource description page.
Title and publication info taken from resource description page (viewed February 12, 2015)
Keywords: Microsoft Visual studio; Cross-platform software development; Mobile apps; Application software; Mobile computing; Applications mobiles; Logiciels d'application; Informatique mobile